KARAKTERISTIK PENDERITA TUBERKULOSIS PARU DI PUSKESMAS WONGEDUKU BARAT KABUPATEN KONAWE - Yusna Dewi; Masrida Baharuddin (-, 2022)
Abstract  Pulmonary tuberculosis (TB) is a disease that is dangerous to health and can cause death if not detected and treated early. West Wongeduku is one of the work areas of the Konawe Health Service which has a high coverage of pulmonary tuberculosis sufferers and has increased every year, namely in 2020 as many as 12 people and in 2021 as many as 20 people. The purpose of this study was to determine the prevalence of cure and characteristics of pulmonary tuberculosis patients at the West Wongeduku Public Health Center. This type of research is an observational study with a descriptive approach. Population is all tuberculosis patients from years 2020 period January and the sample was taken by total sampling amounted to 20 respondents. The data collected is secondary data and analyzed descriptively. Address mapping in patients using Global Positioning System (GPS). The results showed that the prevalence of pulmonary tuberculosis (TB) cure at the West Wongeduku Health Center in Konawe Regency was 33.3% and there were still 66.7% who had pulmonary TB or had not recovered. The age of pulmonary TB patients was mostly in the 50-59 year group as much as 60.0% and a small portion in the 20-29 year age group as much as 5.0%. Then most of the men as much as 70.0%, the rest are women 30.0%. The education of most pulmonary TB patients is junior high school graduates (50.0%) and the least is DIII graduates (5.0%). Furthermore, the work of most pulmonary TB patients is not working as much as 70.0% and a small proportion are private as much as 5.5%. The longest duration of suffering from pulmonary TB was 6 months, namely 75.0%, the rest 6 months as much as 25.0%. Suggestions for the West Wongeduku Health Center to establish policies related to efforts to find new cases, prevention and control of pulmonary tuberculosis (TB) events in the working area of the West Wongeduku Health Center and for pulmonary TB patients it is expected that they routinely undergo treatment and consume packaged medicines given from the Health Center.Keywords : Pulmonary Tuberculosis, Age, Gender, Education, Occupation ABSTRAK Tuberkulosis paru (TB) merupakan penyakit yang berbahaya bagi kesehatan dan dapat menyebabkan kematian jika tidak dideteksi dan ditangani secara dini. Wongeduku Barat merupakan salah satu wilayah kerja Dinas Kesehatan Konawe yang memiliki cakupan penderita tuberkulosis paru yang tinggi dan mengalami peningkatan setiap tahunnya yaitu pada tahun 2020 sebanyak 12 orang dan tahun 2021 sebanyak 20 orang. Tujuan penelitian ini adalah untuk mengetahui prevalensi kesembuhan dan karakteristik penderita tuberkulosis paru di Puskesmas Wongeduku Barat.Jenis penelitian ini adalah penelitian observasional dengan pendekatan deskriptif. Populasi adalah seluruh penderita tuberkulosis dari tahun 2020 periode Januari dan sampel diambil secara total sampling berjumlah 20 responden. Data yang dikumpulkan merupakan data sekunder dan dianalisis secara deskriptif. Pemetaan alamat pada pasien menggunakan Global Positioning System (GPS).Hasil penelitian menunjukkan bahwa prevalensi kesembuhan penyakit tuberkulosis (TB) paru di Puskesmas Wongeduku Barat Kabupaten Konawe sebesar 33,3% dan masih terdapat 66,7% yang menderita TB paru atau belum sembuh. Usia penderita TB paru terbanyak pada kelompok 50-59 tahun sebanyak 60,0% dan sebagian kecil pada kelompok usia 20-29 tahun sebanyak 5,0%. Kemudian sebagian besar laki-laki sebanyak 70,0%, sisanya perempuan 30,0%. Pendidikan penderita TB paru terbanyak adalah lulusan SMP (50,0%) dan paling sedikit lulusan DIII (5,0%). Selanjutnya pekerjaan sebagian besar pasien TB Paru tidak bekerja sebanyak 70,0% dan sebagian kecil adalah swasta sebanyak 5,5%. Lama menderita TB paru terlama adalah 6 bulan yaitu 75,0%, selebihnya 6 bulan sebanyak 25,0%. Saran bagi Puskesmas Wongeduku Barat agar menetapkan kebijakan terkait upaya penemuan kasus baru, pencegahan dan penanggulangan kejadian tuberkulosis (TB) paru di wilayah kerja Puskesmas Wongeduku Barat dan bagi penderita TB paru diharapkan rutin menjalani pengobatan dan mengkonsumsi obat dalam kemasan yang diberikan dari Puskesmas. Kata kunci : Tuberkulosis Paru, Usia, Jenis Kelamin, Pendidikan, Pekerjaan